Lip print enhancement: review - Maxwell Abedi; Constance Afoakwah; Dan Nana Osei Mensah Bonsu (Oxford University Press, 2020)
Lip print (LP) evidence can be an essential tool for human forensics. LPs have conventionally been developed using substances such as lysochrome dyes, fluorescent dyes, indigo dye, aluminium powder, and silver metallic powder. However, techniques for LP enhancement from various substrates are currently inconsistent and lack standardisation in practice. This review summarises current knowledge on the physical and chemical techniques of LP enhancement, identifies limitations, and provides suggestions for future research on practical applications of cheiloscopy as a forensic tool in criminal justice.Key points The grooves and wrinkles of the human lip establish unique patterns that persist throughout life. Cheiloscopic patterns exhibit discriminatory individual characteristics that may constitute circumstantial forensic evidence. Enhancement techniques for latent lip prints on porous and nonporous substrates can be classified as physical or chemical. Unlike fingerprint, there is a current lack of consistency and/or standardisation on latent lip print enhancement methods in frontline forensic practice.